FAKTOR YANG MEMPENGARUHI KEGIATAN PRAKTIKUM BIOLOGI: STUDI PADA PRAKTIKUM STRUKTUR PERKEMBANGAN TUMBUHAN(FACTORS INFLUENCING BIOLOGY PRACTICAL ACTIVITIES: STUDY ON PLANT DEVELOPMENTAL STRUCTURE PRACTICUM) - Anggrella, Dita Purwinda; Hidayah, Nurul; Latifah, Nurul (Universitas Negeri Yogyakarta, 2025)
Biology practicum is an important part of learning that aims to strengthen conceptual understanding through direct experience. This study aims to identify factors that influence biology practicum activities, especially on the material of plant development structure. This study uses a quantitative method with a survey approach, involving 15 students of the Biology Education study program who have participated in the Plant Development Structure practicum. Data were collected through a closed questionnaire with a Likert scale (1-5) and structured interviews with students and lecturers to obtain more in-depth information. The analysis showed that collaboration skills had the highest average (4.53) and were the dominant factor in supporting the smooth running of the practicum. Student motivation also played a significant role (4.13), indicating high enthusiasm for participating in the practicum. Other factors, such as laboratory facilities, use of practicum tools, and time management, had the same average value (3.80), indicating that these factors were quite supportive but still needed improvement. Meanwhile, understanding practicum procedures had the lowest average (3.53) with the highest standard deviation (0.834), indicating significant variation in student understanding. The interview results revealed that limited laboratory facilities, lack of skills in using laboratory equipment, and difficulties in time management were the main obstacles to laboratory activities. Overall, this study highlights the importance of collaboration skills and motivation in supporting the effectiveness of laboratory work. In addition, improvements in understanding procedures and providing more adequate facilities and tools are needed to improve the quality of learning in biology laboratory activities.